UKRAINIAN VERSION OF APPROPRIATENESS EVALUATION PROTOCOL AND CRITERIA OF INPATIENT CARE DURATION - Lekhan, V.N.; Kriachkova, L.V.; Zaiarskyі, M.I.; Borvinko, E.V. (World of Medicine and Biology, 2019)
Most healthcare systems use the Appropriateness Evaluation Protocol (AEP) to analyze the adequacy of inpatient care. As a result of the study, for the first time, according to the Delphi Collective Expert Assessment procedure, Ukrainian indications for inpatient care in hospital and its duration, consisting of four groups of criteria, were developed: severity of the disease, intensity of medical services, medical care / life support services and others; among the latter, the leading place is occupied by the hospitalization indications, defined in national unified clinical protocols.The inpatient care duration is determined on the basis of an individual assessment of the patient's condition dynamics, taking into account indications for hospitalization. The analysis showed high values of validity and reliability of the developed criteria for justification and inpatient care duration, which permits to recommend the Ukrainian version of the protocol hospitalization justification (AEP-UA) for use.
Keywords: Ukrainian version of the hospitalization feasibility assessment protocol (AEP-UA); criteria for hospitalization and its duration